Impediments to biodiversity finance implementation system: A thematic analysis - Ayesha Shehzad; Kanwal Iqbal Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
The global concern of biodiversity loss highlights the significance of sustainable practices protecting natural resources, which require massive investment. However, scarce resources often hinder this, particularly in emerging economies. Biodiversity finance can be an anticipated solution to this burning issue that can ensure the sustainable management of the ecosystem. Still, due to the evolving nature of the concept, its application is restricted to different stages. The current study explores the impediments to biodiversity finance implementation in emerging economies like Pakistan. It is based on a qualitative research design and is conducted in two stages. Initially, an extensive literature review was conducted to clarify the concept of biodiversity finance and identify the impediments reported by prior researchers. Later, twenty-five semi-structured interviews were conducted with the members of financial institutions, NGOs, agencies, policymakers, investors, and subject experts. Finally, the interviews were transcribed and analyzed using NVivo-14. The identified impediments were categorized into seven major themes: conceptual, social, environmental, finance, economic, framework-related, and territorial, and also suggest the future perspective of the concept. The findings suggest that the major hindrances in biodiversity finance adoption are lack of conceptualization, economic and political instability, inadequate funds, social injustice, environmental deregulation, and excess usage of natural resources. The findings will be helpful for financial institutions, NGOs, and agencies in policy-making and framework formulation for successfully applying the biodiversity finance system.
Keywords: 330; Biodiversity finance; sustainable development goals; biodiversity loss; sustainable management; Pakistan